2004
DOI: 10.12702/1984-7033.v04n01a12
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in heterosis of maize populations derived from single-cross hybrids after reciprocal recurrent selection

Abstract: One hundred and sixty-nine interpopulational half sib progenies were obtained from maize populations derived from the commercial single-cross hybrids AG9012 (1) and C333 (2) to investigate the efficiency of reciprocal recurrent selection (RRS). Fifteen progenies with highest hulled ear yield were obtained. Two recombination trials were sown with remnant S 1 seeds, and the improved CI 1 and CI 2 populations were simultaneously obtained with their hybrid combination. Yield trials were set up in three sites to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
2
0
2
Order By: Relevance
“…2009 observa-se coerência com os relatos de SRR presentes na literatura. Trabalhos com populações derivadas de híbridos simples mostraram respostas de 5,7 (Raposo et al, 2004), 4,5 e 6,2% (Coors, 1999) à seleção por ciclo. Em programas com populações temperadas (BS10 e BS11) submetidas à SRR de irmãos germanos por oito ciclos, Eyherabide & Hallauer (1991) reportaram ganho de 6,5% por ciclo.…”
Section: Methodsunclassified
See 1 more Smart Citation
“…2009 observa-se coerência com os relatos de SRR presentes na literatura. Trabalhos com populações derivadas de híbridos simples mostraram respostas de 5,7 (Raposo et al, 2004), 4,5 e 6,2% (Coors, 1999) à seleção por ciclo. Em programas com populações temperadas (BS10 e BS11) submetidas à SRR de irmãos germanos por oito ciclos, Eyherabide & Hallauer (1991) reportaram ganho de 6,5% por ciclo.…”
Section: Methodsunclassified
“…bras., Brasília, v.44, n.12, p.1667-1672, dez. 2009 A SRR com uso de populações derivadas de híbridos simples já se mostrou viável em outras condições (Coors, 1999;Raposo et al, 2004). No entanto, é necessário utilizar um método de SRR que seja mais dinâmico e rápido.…”
Section: Introductionunclassified
“…Similarly, Russell et al (1992) obtained 4.9% in the interpopulation hybrid from the cross between BS21 (R) x BS22 (R) populations during three selection cycles. Raposo et al (2004) and Reis (2013) reported 5.7 and 4.5% increases in grain yield, respectively, after three RRS cycles, in populations from simple hybrids.…”
Section: Genetic Progressmentioning
confidence: 94%
“…It can be seen that CIMMYT populations (Figure 3a) presented lower performance than other genotype groups and production instability along the cycles. A number of authors report that, when it comes to reciprocal recurrent selection, it is common to obtain little or no gain in one of the populations (Keeratinijakal and Lamkey, 1993;Raposo and Ramalho, 2004;Hallauer Carena, 2009;Reis et al, 2013). For the CIMMYT populations, it was verified an increase of 44 kg.ha -1 .cycle -1 of selection and 22 kg.ha -1 .year -1 , of which values are not significant by the t test at 1% probability and an R² of 0.08 (Figure 3).…”
Section: Genetic Progressmentioning
confidence: 99%